Inter-individual differences in the responses to aerobic exercise in Alzheimer's disease: Findings from the FIT-AD trial - Fang Yu; Dereck Salisbury; Michelle A. Mathiason (Elsevier, 2021)
Background: Despite the strong evidence of aerobic exercise as a disease-modifying treatment for Alzheimer's disease (AD) in animal models, its effects on cognition are inconsistent in human studies. A major contributor to these findings is inter-individual differences in the responses to aerobic exercise, which was well documented in the general population but not in those with AD. The purpose of this study was to examine inter-individual differences in aerobic fitness and cognitive responses to a 6-month aerobic exercise intervention in community-dwelling older adults with mild-to-moderate dementia due to AD. Methods: This study was a secondary analysis of the Effects of Aerobic Exercise for Treating Alzheimer's Disease (FIT-AD) trial data. Aerobic fitness was measured by the shuttle walk test (SWT), the 6-min walk test (6MWT), and the maximal oxygen consumption (VO2max) test, and cognition by the AD Assessment Scale-Cognition (ADAS-Cog). Inter-individual differences were calculated as the differences in the standard deviation of 6-month change (SDR) in the SWT, 6MWT, VO2max, and ADAS-Cog between the intervention and control groups. Results: Seventy-eight participants were included in this study (77.4 ± 6.3 years old, mean ± SD; 15.7 ± 2.8 years of education; 41% were female). VO2max was available for 26 participants (77.7 ± 7.1 years old; 14.8 ± 2.6 years of education; 35% were female). The SDR was 37.0, 121.1, 1.7, and 2.3 for SWT, 6MWT, VO2max, and ADAS-Cog, respectively. Conclusion: There are true inter-individual differences in aerobic fitness and cognitive responses to aerobic exercise in older adults with mild-to-moderate dementia due to AD. These inter-individual differences likely underline the inconsistent cognitive benefits in human studies.